Enhancing antitumor immunogenicity of HPV16-E7 DNA vaccine by fusing DNA encoding E7-antigenic peptide to DNA encoding capsid protein L1 of Bovine papillomavirus - Yang, Andrew (Cell Biosci, 2017)
BACKGROUND: Human papillomavirus (HPV) has been identified as the primary etiologic factor of cervical cancer, the fourth leading cause of cancer death in females worldwide. We have previously shown that coadministration of DNA encoding L1 capsid protein of Bovine papillomavirus (BPV) can enhance the antigen-specific immune response elicited by a therapeutic HPV16-E7 DNA vaccination. In this study, we sought to generate and evaluate the immunogenicity of a therapeutic HPV16-E7 DNA vaccine that encodes the fusion construct of HPV16-E7 and BPV-L1. RESULTS: We generated a therapeutic HPV16-E7 DNA vaccine construct, pcDNA3-BPVL1-E7(49-57), encoding the fusion sequence of full-length BPVL1 protein and a murine E7 antigenic epitope, aa49-57. Transfecting 293-D(b) cells with pcDNA3-BPVL1-E7(49-57) demonstrated that this DNA construct can effectively lead to the presentation of E7 epitope for the activation of E7-specific CD8+ T cells in vitro. Intramuscular vaccination of pcDNA3-BPVL1-E7(49-57) with electroporation generated a stronger E7-specific CD8+ T cell-mediated immune response than coadministration of pcDNA3-BPVL1 and pcDNA3-E7(49-57) in C57BL/6 mice. Furthermore, we observed that the strong E7-specific CD8+ T cell response elicited by pcDNA3-BPVL1-E7(49-57) vaccination translated into potent protective and therapeutic antitumor effects in C57BL/6 mice against HPV16-E7 expressing TC-1 tumor cells. Finally, using antibody depletion experiment, we showed that the antitumor immune response generated by pcDNA3-BPVL1-E7(49-57) is CD8+ T cell dependent, and CD4+ T cell and NK cell independent. CONCLUSION: Treatment with fusion construct of BPV-L1 and HPV16-E7 epitope can elicit effective E7-specific antitumor immune response in mice. Due to the potential ability of the fusion DNA construct to also trigger immune responses specific to the L1 protein, the current study serves to support future design of HPV DNA vaccines encoding fusion HPVL1-E6/E7 constructs for the generation of both T cell and B cell mediated immune responses against HPV infections and associated diseases.